Familismo, Lesbophobia, and Religious Beliefs in the Life Course Narratives of Chilean Lesbian Mothers - Figueroa, Victor; Tasker, Fiona (Frontiers in Psychology, 2020)
This study aimed to explore the life course identity projects of Chilean lesbian mothers who conceived their children within the context of a previous heterosexual relationship. By exploring the case of Chile, this study examined the family lives of lesbian mothers within the context of a Latino heteronormative society with a Christian (mainly Catholic) heritage. Individual interviews were conducted with eight participants aged between 27 to 40 years old (mean age of 33 years) who were recruited through snowballing and social media. A Structural Narrative Analysis of participants’ stories was conducted within a Life Course Perspective theoretical framework. The study found that participants initially followed a heterosexual path to conform to their family of origin and social expectations. After building their own heterosexual family projects and having their children with a man, most participants felt pressured to continue within a heterosexual path and postponed their transition to a lesbian identity trajectory despite a growing feeling that a lesbian identity would be personally fullfilling. Although participants felt proud of their identities, they struggled to express their same-gender feelings because lesbians were often seen as inappropriate models for children within Chilean society. Crucially, lesbian mothers continued to be able to count upon support for their parenting from their own mother despite intense disapproval from their family of origin and often continued opposition from ex-husbands/partners. The findings of this study revealed the strong impact of familismo, lesbophobia and Christian religious beliefs on the life course experiences of Chilean lesbian mothers. Implications for therapy and counselling with lesbian mothers living in Latino countries are reviewed.